Colonial governmentality and the political thinking through “1931” in the Crown colony of Ceylon/Sri Lanka - Nira Wickramasinghe (Socio, 2015)
This paper uses the Arendtian notion of the “political” to argue that the colonial framework and modernity have for long overdetermined the way historians have analyzed the “political” in South Asia. Using 1931—the year universal suffrage was introduced to the Crown colony of Sri Lanka—as an entry point, it engages critically yet constructively with the subaltern studies school’s creative adaptation of Foucault’s notion of governmentality, as well as the seminal work of David Scott on colonial governmentality in Sri Lanka. It identifies a real need for seeking new strategies to understand the failure of the disciplinary technologies and governmentalized modern technologies to produce modern rational subjects. Is the solution then as Fred Cooper suggests“ to do history historically” and simply trade notions such as “colonial modernity” and “colonial governmentality” for multiple agents, actions, forces and processes of historical explanations?